Agenstvo novostei kul'tury . Agenstvo novostei kul'tury . Agency of Cultural News . Агентство новостей культуры - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Segment on theater actress Galina Vishnevskaia; 50th birthday of the writer Mikhail Zhvanetskii; poetry evening, devoted to the poet Arseny Tarkovskii; talk with a pop singer Tatiana; exhibition "Heritage of Russian Emigration, 1917-1949 in Moscow; survey of the news of pop culture. Featured in the program: Zhvanetskii, Mikhail Mikhailovich (Writer) Сюжет о театральной актрисе Галине Вишневской; 50-летие писателя Михаила Жванецкого; поэтический вечер, посвященный поэту Арсению Тарковскому; выставка "Наследие русской эмиграции 1917-1940х гг. в Москве; обзор новостей популярной культуры. В программе участвуют: Жванецкий, Михаил Михайлович (Писатель)